Effect of Composition and Preparation Method of (Pd), Co, Ce, Zr – Metal-Oxide Catalysts on their Activity in the Reduction of Nitrogen(I), (II) Oxides with Carbon Monoxide - T. M. Boichuk; P. I. Kirienko; S. M. Orlyk; S. O. Soloviev (Хімія, фізика та технологія поверхні)
Among the studied (Pd), Co-, Ce-, Zr-oxide catalysts including catalysts deposited on structured cordierite support, the catalyst prepared by co-deposition of ceria and cobalt oxide is characterized by higher activity in reaction of reduction of nitrogen (I), (II) oxides (CO + NO, N2O + NO + CO) compared with samples prepared by successive deposition. This may be caused by an increase in both mobility of surface oxygen and dispersity of components in the catalytic composition.